015 Mitochondrial cyclophilin-D as a therapeutic target for post-myocardial infarction heart failure. (22nd September 2015) - Lim, S Y; Arjun, S; Price, A N; Davidson, S M; Lythgoe, M F; Hausenloy, D J; Yellon, D M
Abstract : Introduction: The pharmacological inhibition or genetic ablation of mitochondrial cyclophilin-D (CypD), a critical regulator of the mitochondrial permeability transition pore (mPTP), confers myocardial resistance to acute ischaemia-reperfusion injury. Whether targeting mitochondrial CypD is beneficial in post-myocardial infarction heart failure is unknown and is the subject of the current investigation. Methods and Results: Wild type (WT) and CypD deficient (CypD−/−) mice were subjected to either sham surgery or left anterior descending coronary artery ligation. After 2 days, in the CypD−/− mice, when compared to the WT mice, myocardial infarct size measured by cardiac MRI was smaller (27.6±4.7% CypD−/− vs 40.4±1.5% WT:p<0.05:N>5) and left ventricular ejection fraction measured by echocardiography was better preserved (66.4±2.5% CypD−/− vs 55.8±1.6% WT:p<0.05:N>10). At 28 days post-MI in the CypD−/− mice, when compared to the WT mice, mortality was halved (Survival=83% (10/12) CypD−/− vs 44% (10/23) WT:p<0.05), myocardial infarct size measured by histology was reduced (21.3±1.3% CypD−/− vs 33.9±4.3% WT:p<0.05:N=10), LV systolic function measured by echocardiography was better preserved (ejection fraction=58.8±2.8% CypD−/− vs 41.0±2.8% WT:p<0.05:N=10), LV dilatation measured by echocardiography was attenuated and there was less cardiomyocyte hypertrophy and interstitial fibrosis in the remote myocardium. Finally, ex vivo fibroblast proliferation was found to be reduced in CypD−/− cardiac fibroblasts and in WT cardiac fibroblasts treated with the known CypD inhibitors, ciclosporin-A and sanglifehrin-A. Conclusions: Following myocardial infarction, CypD−/− mice have less mortality, experience smaller infarct sizes, have better preserved LV systolic function, and undergo less adverse LV remodelling. These findings suggest that mitochondrial CypD may be a novel therapeutic target for the treatment of post-myocardial infarction heart failure.